Participants’ perspectives and preferences on clinical trial result dissemination: The TRUST Thyroid Trial experience [version 2; peer review: 2 approved] - Emmy Racine; Caroline Hurley; Aoife Cheung; Carol Sinnott; Karen Matvienko-Sikar; Christine Baumgartner; Nicolas Rodondi; William H. Smithson; Patricia Kearney (HRB Open Research, 2019)
Background: While there is an increasing consensus that clinical trial results should be shared with trial participants, there is a lack of evidence on the most appropriate methods. The aim of this Study Within A Trial (SWAT) is to use a patient and public involvement (PPI) approach to identify, develop and evaluate a patient-based approach to receiving trial results for participants in the Thyroid Hormone Replacement for Subclinical Hypo-Thyroidism Trial (TRUST), a trial of thyroxine versus placebo in people aged 65 years and older. Methods: Mixed methods study with three consecutive phases. Phase 1 iteratively developed a patient-based approach using semi-structured focus groups and a consensus-orientated-decision model, a PPI group to refine the method and adult literacy review for plain English assessment. Phase 2 was a single-blind parallel group trial. Irish TRUST participants were randomised to the intervention (patient-based approach) and control group (standard approach developed by lead study site). Phase 3 used a patient understanding questionnaire to compare patient understanding of results between the two groups. Results: Participants want to receive results of clinical trials, with qualitative findings indicating three key themes including ‘acknowledgement of individual contribution’, ‘contributing for a collective benefit’ and ‘receiving accessible and easy to understand results’. Building on these findings, the patient-based approachwas developed. TRUST participants (n=101) were randomised to the intervention (n=51) or control group (n=50). The questionnaire response rate was 74% for the intervention group and 62% for the control group.  There were no differences in patient understanding between the two approaches.  Conclusions: We have demonstrated that it is feasible to involve trial participants in the development of result dissemination materials. Although, in this study PPI did not influence patients’ understanding of results, it documents the process of conducting PPI within the clinical trial setting.